2011
DOI: 10.1097/hjh.0b013e328342ca97
|View full text |Cite
|
Sign up to set email alerts
|

Better compliance to antihypertensive medications reduces cardiovascular risk

Abstract: In the real life setting, fulfillment compliance with antihypertensive medications is effective in the primary prevention of cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
1
25

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 303 publications
(251 citation statements)
references
References 51 publications
7
218
1
25
Order By: Relevance
“…Pharmacological methods include antihypertensive medications daily [9][10][11]. This is increasingly coupled with measures to enhance adherence to the medicines prescribed given current concerns, coupled with other measures to reduce morbidity and mortality [1,12,13]. Non-pharmacological methods include restricting sodium intake to 80-100 mmol/day, weight loss, exercise and dietary changes [8,14] as well as stress reduction through relaxation methods such as yoga [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological methods include antihypertensive medications daily [9][10][11]. This is increasingly coupled with measures to enhance adherence to the medicines prescribed given current concerns, coupled with other measures to reduce morbidity and mortality [1,12,13]. Non-pharmacological methods include restricting sodium intake to 80-100 mmol/day, weight loss, exercise and dietary changes [8,14] as well as stress reduction through relaxation methods such as yoga [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our dose‐response analysis of PDC and risk for CVD events suggested a threshold effect of PDC at around 80%. Some studies also reported insignificant risk reduction comparing the intermediate adherence (40–79%) to low adherence (<40%),13, 19, 38 but others reported more‐gradual risk reduction associated with increased adherence 39, 40, 41. The reasons for the discrepancies in risk reduction are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that nonadherence to pharmacological therapy is the pivotal challenge of successful blood pressure (BP) control because antihypertensive therapy implies, in most cases, a lifelong treatment 1, 2, 3, 4. Several outcome research studies found that nonadherence to antihypertensive agents significantly increased cardiac and cerebrovascular risk 5, 6, 7. Furthermore, the choice of prescribed drug class affects adherence rates of antihypertensive therapies 8, 9.…”
Section: Introductionmentioning
confidence: 99%